Comparison of the Antifungal Activity of Honey and Fluconazole against Candida albicans in vitro and in an Enteric Candidiasis Mouse Model - Mousa Majidi Poya; Alireza Khodavandi (Journal of Advanced Biomedical Sciences, 2018)
Background & Objective: Candidiasis has gained importance due to its increasing prevalence in immunocompromised patients. Antifungal drugs such as fluconazole and amphotericin B are used for the treatment of candidiasis. One of the biggest problems faced in clinical practice is resistance for most of these drugs. The antifungal drugs derived from natural products have helped to overcome this problem. This study evaluated the effects of Kohgiluyeh and Boyer-Ahmad natural honey and fluconazole on C. albicans in an enteric candidiasis mouse model. Materials & Methods: The in vitro antifungal activity of honey samples from different sources were evaluated for their ability to inhibit the growth of C. albicans. Time kill test was carried out to evaluate the anticandidal activities of the honey tested. Eventually, the efficacy of the best honey tested compared with fluconazole against C. albicans was evaluated in vivo through an enteric candidiasis mouse model. Results: The results revealed that the honey tested was able to inhibit C. albicans. Our data indicated that oak honey largely represented antifungal activity among the honey tested (p≤ 0.001). Treatment of BALB/c mice infected with C. albicans showed that treatment with honey was slightly less efficacious than fluconazole treatment in terms of the fungal load reduction, it was still effective against C. albicans. Conclusions: These results demonstrate the efficacy of anticandidal effects of honey extracts both in vitro and in an animal model of candidiasis and affirm the potential of honey to be used as an adjuvant therapy in the management of Candida infections.